Systemic Sclerosis is Not Associated with Increased Coronary Artery Calcium Deposition - Lee SEUNG-GEUN,; Park YOUNG-EUN,; Choi SU-YEON,; Park EUN-KYUNG,; Kim GEUN-TAE,; Choo KI-SEOK,; Jeong YEON-JOO6, (Archives of Rheumatology, 2013)
Objectives: This study aims to compare the coronary artery calcium scores (CACS) between female systemic sclerosis (SSc) patients and healthy subjects and to investigate whether SSc alone is an independent risk factor for increased coronary artery calcium deposition. Patients and methods: Between January 2007 and December 2009, 41 female SSc patients and 123 age- and gender-matched healthy subjects who were admitted to a tertiary healthcare center in South Korea were retrospectively analyzed. The CACS were measured using multidetector computed tomography (MDCT) and categorized as either absent (CACS=0), minimalto- mild (CACS=1-100), or moderate-to-severe (CACS≥101). We also collected data from each patient related to conventional cardiovascular risk factors. Results: There was no significant difference in the CACS and the proportion of minimal-to-mild and moderate-to-severe coronary calcium deposition between the two groups (p=0.519 and p=0.242, respectively). Multivariable logistic regression analysis revealed that SSc was not independently associated with the presence of coronary calcium deposition (CACS >0) after confounding factors were adjusted. Although SSc was more likely to have a higher category of CACS in the multivariable ordinal logistic regression model (OR 2.79, 95% CI 0.92-8.49, p=0.07), this did not reach statistical significance. Among traditional risk factors, only older age was significantly associated with increased coronary calcium deposition. Conclusion: Our study results suggest that SSc is not an independent risk factor for atherosclerosis.